Evaluation of nanometer thick mercury film electrodes for stripping chronopotentiometry - Rocha, L. S. (2013)
In this work, the performance and applicability of the thin mercury film electrode (TMFE) in the heavy metal speciation, by stripping chronopotentiometry (SCP), were exploited. The TMFE thickness was optimized and a 7.6 nm mercury film was selected. This TMFE was mechanically stable and able to perform 60 SCP consecutive measurements, with no significant variation in the analytical signal of lead(II) (RSD less than 2%). Due to the small electrode thickness the measurements were performed under conditions of complete depletion over a wide oxidation current (Is) range, i.e., within the interval [75–500] × 10−9 A. The limit of detection (3σ) for lead(II) was 2.4 × 10−9 M for a deposition time of 40 s and an oxidation current of 75 × 10−9 A. The TMFE was successfully applied to the construction of SSCP experimental waves, which were in conformity to those predicted by the theory. The stability constant calculated (K′) for the Pb(II)-carboxylated latex nanospheres system using a TMFE, agreed with the one obtained using the HMDE, for identical experimental conditions.